The Relationship Between Personality Type and Leadership Style Among The Nurses In The Adventist Hospital of Bandar Lampung - Alicia Pricillia Elisabeth Serenity Putri Nayoan; Novita Verayanti Manalu (Syntax Corporation, 2022)
Being two of the many factors that affect leadership influencing the result of patients’ health care delivery, personality type and leadership style are often mentioned. Personality types mark certain traits a person may have as well as how leadership style varies based on the individual. Each individual is believed to have the potential to be a leader, especially in nursing care setting. Therefore, this study is carried out among nurse workers to discover the relationship between these two variables which may enhance the efficiency of care delivery through obtaining deeper understanding of the nurses’ personality types and leadership styles. This study is accomplished using a quantitative cross-sectional design that acquired its data from nurse respondents working in the Adventist Hospital of Bandar Lampung. The respondents filled two questionnaires assessing their personality types and leadership types which was analyzed using Pearson Correlation and Sig. (two tailed) by SPSS to find the correlation between the two variables. Majority of the participants are females, age raging from 36-45. It is found that the most common type of personality among the participants are phlegmatic while the most frequent leadership style found is democratic. According to the data processed, there is a strong and significant relationship between the personality types and leadership styles among the nurse respondents. Knowing the personality types and leadership styles used by nurses provide themselves a better self-understanding which allows nurses to know their strength and weaknesses to work on. Most of the nurses are found to have phlegmatic personality type and democratic leadership style. It is recommended that the future researchers may carry out researches on this topic and study the variables’ relationship with another variable, such as work satisfaction